Analisis Penggunaan Ninshou Daimeishi pada Film Rurouni Kenshin Karya Nobohiro Watsuki (Tinjauan Kajian Sosiolinguistik) - Alfiansyah Hakiki; Yuni Masrokhah (KIRYOKU, 2022)
This research is entitled Analysis of the Use of Ninshou Daimeishi in Nobuhiro Watsuki's Rurouni Kenshin Film (Sociolinguistic Review). Ninshou Daimeishi is a type of word that is used to indicate an object or person that also replaces the person's name. The purpose of this study is (1) to describe the Ninshou Daimeishi contained in the film Rurouni Kenshin by Nobuhiro Watsuki. (2) To conclude the factors behind the use of ninshou daimeishi in the film Rurouni Kenshin by Nobuhiro Watsuki. The main theory used in this study regarding ninshou daimeishi is Terada, while the supporting theory used is about linguistics, sociolinguistics, and others. This study uses a qualitative descriptive method, while the source of the data used in this study is a film with the title Rurouni Kenshin by Nobuhiro Watatsuki found as many as 110 sentences containing ninshou daimeishi. The data analysis technique used in this study is to use the listening and note-taking technique. The results of this study are expected to be able to answer the questions and objectives of the research..